An age-period-cohort analysis of trends in psychedelic and ecstasy use in the Australian population. (April 2022) - Chan, Gary; Sun, Tianze; Lim, Carmen; Yuen, Wing See; Stjepanović, Daniel; Rutherford, Brienna; Hall, Wayne; Johnson, Ben; Leung, Janni
Highlights: MDMA use peaked at the 1971–80 birth cohort and decreased for the 1981–90 and 1991–2001 cohort. Psychedelics use of the 1971–80, 1981–90 and 1991–2001 cohorts was similar and higher than earlier birth cohort. Psychedelic use increased between 2001 and 2019. MDMA use peaked at 2007 and dropped slightly in subsequent years. Abstract: Aim: To test the age, cohort, and period effect on past-year use trends in psychedelic drugs and ecstasy. Method: Data were from a repeated cross-sectional nationally representative household survey in Australia conducted every three years between 2001 and 2019. An age-period-cohort model was used to test the effect of age, birth cohort, and period on past year psychedelic and ecstasy use. Participants were between 18 and 80 years old at the time of the survey. The total sample size was 149, 296 (Mean age = 45.8; 56% female). Past-year use of psychedelics and ecstasy were the key outcome variables. There were six birth cohorts that were derived in each survey: 1936–50, 1951–60, 1961–70, 1971–80, 1981–90, and 1991–2001. There were seven periods that coincided with survey years: 2001, 2004, 2007, 2010, 2013, 2016 and 2019. Age was treated as continuous. Results: Past-year use of both psychedelics and ecstasy decreased with age, b  = −0.87, 95% CI [−1.14, −0.61] and b  = −0.84, 95% CI [−1.08, −0.60]. For ecstasy, while there was significant variation across periods ( p  < .001), there was no obvious trend. There was a significant birth cohort effect ( p  < .001), with prevalence increasing from the 1936–50 cohort, peaking in the 1971–80 cohort and then decreasing in the 1991–2001 cohort. For psychedelics, there was significant variation across periods ( p  < .001) with an upward trend. There was a significant birth cohort effect ( p  < .001), with prevalence increasing from the 1936–50 cohort to similarly high prevalence for the three most recent cohorts (1971–80, 1981–90, 1991–2001). Conclusion: There were strong cohort and period effects in trends in the use of psychedelic and ecstasy.